2013
DOI: 10.1186/1741-7015-11-65
|View full text |Cite
|
Sign up to set email alerts
|

A multifactorial interdisciplinary intervention reduces frailty in older people: randomized trial

Abstract: BackgroundFrailty is a well known and accepted term to clinicians working with older people. The study aim was to determine whether an intervention could reduce frailty and improve mobility.MethodsWe conducted a single center, randomized, controlled trial among older people who were frail in Sydney, Australia. One group received an intervention targeting the identified characteristics of frailty, whereas the comparison group received the usual health care and support services. Outcomes were assessed by raters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
359
2
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 343 publications
(387 citation statements)
references
References 20 publications
10
359
2
6
Order By: Relevance
“…This fact was observed in other studies, which revealed prevalence of white people among the subjects who participated in the analysis. (13) The reason for the prevalence of frail elderly of white ethnicity can be because the evaluations were carried out at various locations in order to cover different socioeconomic and demographic classes.…”
Section: Discussionmentioning
confidence: 99%
“…This fact was observed in other studies, which revealed prevalence of white people among the subjects who participated in the analysis. (13) The reason for the prevalence of frail elderly of white ethnicity can be because the evaluations were carried out at various locations in order to cover different socioeconomic and demographic classes.…”
Section: Discussionmentioning
confidence: 99%
“…Along with sarcopenia, skeletal muscle fat infiltration, which is assessed through muscle tissue attenuation, is associated with an increased risk of mobility loss in older men and women (Visser et al 2005). As a consequence of impaired muscle function, the diagnosis of frailty includes physical impairments, such as low gait speed, fatigue, and low grip strength (Fried et al 2001;Bandeen-Roche et al 2006;Garcia-Garcia et al 2011;Cameron et al 2013). Due to the physical domains that are related to frailty, physical activity is one of the most important components in the prevention and treatment of this syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive geriatric assessment followed by an individualised multicomponent treatment has a strong evidence base and so not surprisingly is effective when applied to frail older adults. Recent frailty focused trials utilize a range of treatments, including nutritional therapy, psychiatrist or psychologist input, interventions to reduce social isolation, and exercise therapy and show effects [110,111]. One recent trial however showed that the effects take time to accrue so interventions need to be long term.…”
Section: Treatment Strategiesmentioning
confidence: 99%